Die Mar̈kte fur̈ Schlachtvieh und Fleisch - Friedrich-Wilhelm Probst (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2002)
– Agricultural Markets at The Turn of 2001/2002: (5) Meat MarketsInternational red meat markets were rarely more disturbed by animal diseases than in 2000/01. Western Europe and Latin America were directly hit and many other countries declared embargoes. In several EU member countries consumer demand for beef broke off at times by up to 70 per cent heavily straining cattle prices and producer incomes. The EU took various measures to counter such effects among which a "purchase for destruction" scheme, public intervention and an increase of the advances for the beef premia. World pig meat production increased by around 4 per cent in 2001 and trade in meat and live animals rose to almost 10 per cent of production. China is by far the world's biggest supplier yet with only decreasing exports. Pig prices reached cyclical heights during the first half of the year and weak-ened sharply in the US as well as in the EU.
Keywords: 330